Investigation of Elaeocarpus ganitrus seed (EGs) powder as a sustainable composite biomaterial: Effects of particle size on the mechanical, frictional, and thermal properties for potential biomedical applications - Rahmat Doni, Widodo; Rusiyanto, Rusiyanto; Kriswanto, Kriswanto; Rizqi Fitri, Naryanto; May Boy, Alfres; Deni Fajar Fitriyana, .; Siregar, Januar Parlaungan; Rizalman, Mamat; Jamiluddin, Jaafar; Muhammad Imam, Ammarullah (American Institute of Physics, 2024)
This study explores the potential of Elaeocarpus ganitrus seed (EGs) powder as a sustainable composite biomaterial, focusing on its particle size effects on the mechanical, frictional, and thermal properties of composite materials for potential biomedical applications such as prosthetics and implants. Composite specimens were produced using the compression hot molding method, utilizing EG powder particles of varying sizes (120, 140, and 200-mesh sieving). The influence of EG powder particle size on key properties was systematically investigated. The findings reveal that reducing the particle size of EGs leads to a decrease in density and hardness of the composite, with the largest particle size (BP1) resulting in the highest density and hardness. Friction coefficient measurements indicated suitability for biomedical applications where surface interaction and wear resistance are critical, such as joint prosthetics. Thermal analysis showed that BP1 exhibited superior thermal stability, with a maximum decomposition temperature (Tmax) exceeding 375 ○C. Differential scanning calorimetry identified significant differences in glass transition temperature (Tg) and crystallization temperature (Tc) across specimens. The composites demonstrated exceptional thermal performance, surpassing previous benchmarks for biomaterials in high-temperature environments. The mechanical and thermal characteristics of Specimen BP1—2.725 g/cm3 density, 74 Shore D hardness, 0.159 coefficient of friction, 93.3% total residual, 378.14 ○C Tmax, 426.25 ○C Tc, and 376.87 ○C Tg—suggest its potential for biomedical applications requiring durability and thermal resilience, such as in orthopedic devices and tissue engineering scaffolds.